Pathological Effects Of Induced Stress On The Lymphoid Organs Inb Broiler Chicken - Suraj S (Centre of Excellence in Pathology, College of Veterinary and Animal Sciences, 2002)
The experiment was designed to study the pathology of induced stress in broiler chicken and to identify suitable markers for recognition of stress. One hundred and two, day old broiler chicks were divided into three groups of 34 birds each. Birds of Group I was administered dexamethasone orally at the rate of 50 ppm on the 20th day followed by 25 ppm on days 27, 34, 41 and 44. Group II was stocked at higher density of 0.25 if/bird till 28th day and then at 0.5 felbird, while Group III served as control. Behavioural changes, production parameters, haemogram, immunological parameters, and pathological changes in the organs were recorded to study the pathology and to identify suitable markers of stress. Birds of Group I were depressed and developed mild infection while \ Group II showed poor feather development and hyper responsiveness to stimuli initially followed by depression and lameness. Birds of Group I and II showed lower body weights and feed efficiency except for Group II• on the 21st day when higher body weights and better feed efficiency was observed. Leukocytosis, lower values for RBC, haemoglobin and VPRC along with heterophilia, lymphopenia and higher heterophil to lymphocyte ratio were t- recorded for both the stressed groups. Basophilia was observed towards the end . of the experiment in Group II.